Integrated modelling for evaluation of climate change impacts on agricultural dominated basin - Zhang, Rong (2015)
Abstract: This study evaluated future climate change impacts on water resources, extreme discharges and sediment yields for the medium-sized (705-km2) agriculture dominated Cobres basin, Portugal, in the context of anti-desertification strategies. We applied the physically-based spatially-distributed hydrological model—SHETRAN, obtaining the optimized parameters and spatial resolution by using the Modified Shuffled Complex Evolution (MSCE) method and the Non-dominated Sorting Genetic Algorithm II (NSGA-II), to simulate the hydrological processes of runoff and sediment transport. We used the model RanSim V3, the rainfall conditioned weather generator—ICAAM-WG, developed in this study, based on the modified Climate Research Unit daily Weather Generator (CRU-WG), and SHETRAN, to downscale projections of change for 2041–2070, from the RCM HadRM3Q0 with boundary conditions provided by the AOGCM HadCM3Q0, provided by the ENSEMBLES project, under SRES A1B emission scenario. We found future climate with increased meteorological, agricultural and hydrological droughts. The future mean annual rainfall, actual evapotranspiration, runoff and sediment yield are projected to decrease by the orders of magnitude of respectively ~88 mm (19%), ~41 mm (11%), ~48 mm (50%) and ~1.06 t/ha/year (45%). We also found reductions in extreme runoff and sediment discharges, for return periods smaller than 20 years; however for return periods in the range of 20–50 years, future extremes are of the same order of magnitude of those in the reference climate; Modelação integrada para avaliação dos impactos das alterações climáticas sobre bacias hidrográficas com uso predominantemente agrícola Resumo: Neste estudo são avaliados os impactos futuros das alterações climáticas nos recursos hídricos e em extremos do escoamento e transporte de sedimentos, na bacia hidrográfica do rio Cobres, Portugal, agrícola, de dimensão média (705 Km2), no contexto do combate à desertificação. Foi aplicado o modelo hidrológico fisicamente baseado e espacialmente distribuído SHETRAN, tendo sido obtidos os valores optimizados de parâmetros e da resolução espacial, utilizando o método “Modified Shuffled Complex Evolution” (MSCE) e o algoritmo “Non-dominated Sorting Genetic Algorithm II” (NSGA-II), para simular os processos hidrológicos de escoamento e transportes de sedimentos. Foram utilizados o modelo de RainSim V3, o gerador de tempo ICAAM-WG, desenvolvido neste estudo, baseado no CRU-WG, e o SHETRAN, para o “downscaling” das projecções climáticas para 2041 – 2070, geradas pelo MRC HadRM3Q0 com condições de fronteira fornecida pelo MCG HadCM3Q0, projecto ENSEMBLES, sob o cenário SRES A1B. O clima futuro é caracterizado por um número crescente de secas meteorológicas, agrícolas e hidrológicas. Os valores médios anuais da precipitação, evapotranspiração real, escoamento superficial e transporte de sedimentos, revelam decréscimos com ordens de grandeza respectivamente de ~88 mm (19%), ~41 mm (11%), ~48 mm (50%) e ~1.06 t/há/ano (45%). Encontraram-se ainda reduções nos valores extremos do escoamento superficial e do transporte de sedimentos para períodos de retorno inferiores a 20 anos; contudo, para períodos de retorno no intervalo 20–50 anos, os valores extremos futuros apresentam a mesma ordem de grandeza que os relativos ao período de referência mas mantendo níveis equivalentes para os com 20–50 anos.